Sustainable Planning of a New City in Mozambique - Coutinho, Pedro Bettencourt (Brazilian Journal of Operations & Production Management, 2018)
Careful Land and Urban planning is of extreme importance in developing countries with fast growing population like Mozambique. Environmental Strategic Assessment (SEA) and Environmental and Social Impact Assessment (ESIA) are management instruments to early predict urban development potential impacts and risks, contributing to support the shaping of sustainable planning, and avoiding the social and environmental havoc of inadequate development. The objective of this paper is to present the contribution of SEA and ESIA in the planning process of a new major city in southern Mozambique, in Katembe district, facing Mozambique’s capital Maputo. The Katembe City’s environmental and social assessment process highlighted the environmental, socioeconomics and cultural particularities of this territory and identified the critical constraints for urban development. A preliminary assessment avoided major negative potential impacts, but required specific environmental and social detailed studies to be addressed in the new city’s partial urban plans. When these studies were completed the new urban detailed plans included all the necessary environmental requirements to avoid/mitigate flooding, coastal erosion, and biodiversity loss and habitat fragmentation. It is expected that this experience will encourage the wider application of sustainable urban planning in shaping new urban areas in Mozambique and other fast developing countries.